Application of Mind Mapping to Increase Student Creativity in Class IV Science Learning at SDN Pacentan 3 - Camila Faradisa; Siti Auliyatil Karomah; Neni Novitasari (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2025)
This research is motivated by the low creative thinking ability of students in elementary science learning, the learning tends to be boring, and orientation on the ability of teachers who only teach knowledge, not on analytical, synthetic, and creative abilities. Based on this background, this study aims to improve students' creative thinking skills in elementary science learning. The type of research used in this research is Classroom Action Research with the Kemmis and Mc Taggart model which consists of several stages, namely planning, implementation, observation, and reflection. The data analysis technique is descriptive qualitative using the percentage technique. and the determined success criteria is the score exceeds > 75%. The results of this study indicate an increase in creative thinking skills from the pre-cycle results of 40% with the category increasing in the first cycle, namely 70% and the final result increasing by 100%.